A Robust Control Strategy for Distributed Generations in Islanded Microgrids - esmaeel rokrok; fariba shavakhi zavareh; jafar soltani; mahmoud reza shakarami (AUT Journal of Electrical Engineering)
This paper presents a robust control scheme for distributed generations (DGs) in islanded mode operation of a microgrid (MG). In this strategy, assuming a dynamic slack bus with constant voltage magnitude and phase angle, nonlinear equations of the MG are solved in the slack-voltage-oriented synchronous reference frame, and the instantaneous active and reactive power reference for the slack bus is obtained at each time step, based on Y_bus equation of the MG. The slack bus power references are robustly tracked by the proposed adaptive sliding mode based power controller. In addition, a hyper-plan sliding controller is suggested for other DGs that provides three regulators including active power, reactive power and voltage regulator for DG units and ensures protection of the power electronic interfaces to the faults assumed to have occurred in the MG. At each step time, DGs are modeled as positive and negative current sources that are controlled by their adaptive sliding mode controllers in the normal and abnormal operating conditions. All the parameters of controllers are derived via particle swarm optimization (PSO) algorithm in order to minimize an appropriate cost function. Performance of the proposed control strategy is compared to the performance of the conventional master-slave based control strategy. The validity and effectiveness of the presented method are supported by time domain simulation of a test microgrid in MATLAB.